Marginalized legal categories: Social inequality, family structure, and the laws of intestacy. Issue 2 (27th May 2021) - Bea, Megan Doherty; Taylor Poppe, Emily S.
Abstract: Social classifications are increasingly interrelated, far‐reaching, and consequential for socioeconomic outcomes. We use the concept of marginalized legal categories to describe how the law disadvantages individuals or groups by transforming inherently ordered social classifications into consequential legal categories, employing intestacy laws as an illustration. Using the Survey of Consumer Finances, we find that more than 21% of American families have forms that are marginalized by intestacy classifications, and that such forms are more common among individuals of color and those with less wealth. Yet, many individuals with these family structures hold assets and lack access to intestacy‐avoidance mechanisms, giving consequence to the application of these laws. We conclude by discussing implications of legal classification for inequality.